The Tropical Invasive Seagrass, Halophila stipulacea, Has a Superior Ability to Tolerate Dynamic Changes in Salinity Levels Compared to Its Freshwater Relative, Vallisneria americana - Oscar, Michelle A.; Barak, Simon; Winters, Gidon (Frontiers in Plant Science, 2018)
The tropical seagrass species, Halophila stipulacea, originated from the Indian Ocean and the Red Sea, subsequently invading the Mediterranean and has recently established itself in the Caribbean Sea. Due to its invasive nature, there is growing interest in understanding this species' capacity to adapt to new conditions. One approach to understanding the natural tolerance of a plant is to compare the tolerant species with a closely related non-tolerant species. We compared the physiological responses of H. stipulacea exposed to different salinities, with that of its nearest freshwater relative, Vallisneria americana. To achieve this goal, H. stipulacea and V. americana plants were grown in dedicated microcosms, and exposed to the following salt regimes: (i) H. stipulacea: control (40 PSU, practical salinity units), hyposalinity (25 PSU) and hypersalinity (60 PSU) for 3 weeks followed by a 4-week recovery phase (back to 40 PSU); (ii) V. americana: control (1 PSU), and hypersalinity (12 PSU) for 3 weeks, followed by a 4-week recovery phase (back to 1 PSU). In H. stipulacea, leaf number and chlorophyll content showed no significant differences between control plants and plants under hypo and hypersalinities, but a significant decrease in leaf area under hypersalinity was observed. In addition, compared with control plants, H. stipulacea plants exposed to hypo and hypersalinity were found to have reduced below-ground biomass and C/N ratios, suggesting changes in the allocation of resources in response to both stresses. There was no significant effect of hypo/hypersalinity on dark-adapted quantum yield of photosystem II (Fv/Fm) suggesting that H. stipulacea photochemistry is resilient to hypo/hypersalinity stress. In contrast to the seagrass, V. americana exposed to hypersalinity displayed significant decreases in above-ground biomass, shoot number, leaf number, blade length and Fv/Fm, followed by significant recoveries of all these parameters upon return of the plants to non-saline control conditions. These data suggest that H. stipulacea shows remarkable tolerance to both hypo and hypersalinity. Resilience to a relatively wide range of salinities may be one of the traits explaining the invasive nature of this species in the Mediterranean and Caribbean Seas.